The Disharmony Of The Relationship Between God, Man, And Nature: A Description Of Kali Yuga In The Text Roga Sanghara Bhumi - Putu Sabda Jayendra (IAHN-TP Palangka Raya, 2023)
Hinduism holds on to the concept of Tri Hita Karana which teaches humans to strive for harmonization of the relationship between Ida Sang Hyang Widhi Wasa (God), fellow humans, and the universe. Nevetheless, on the other hand, today phenomenon shows disharmony of the relationship between the three. This is the main characteristic of the Kali Yuga era which has been described clearly in the text Roga Sanghara Bhumi. Roga Sanghara Bhumi describes that human morality will reach its lowest point in the era of Kali Yuga and further away from moral and human values. The implication is of the disharmony is the emergence of epidemics and natural disasters, where even the Yadnya ceremony performed by humans will be in vain. In this context, an understanding of the description of Roga Sanghara Bhumi should be introspection for humanity and behavior improvement in order to make harmony in the future. Keywords: Disharmony, Kali Yuga, Roga Sanghara Bhumi.